2015
DOI: 10.3126/jsan.v1i2.13571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative analgesic effectiveness of combined intraperitoneal instillation and periportal infiltration of bupivacaine with intraperitoneal instillation or periportal infiltration alone for laparoscopic cholecystectomy

Abstract: Background: Visceral pain is the major component of pain after laparoscopic cholecystectomy. Periportal infiltration and peritoneal instillation of local anesthetics have been reported to be effective in various laparoscopic procedures. Aim of this study was to find out the analgesic effectiveness and duration of analgesia following combined intraperitoneal instillation and periportal infiltration of bupivacaine and to compare it with peritoneal instillation or periportal infiltration alone.Methods: A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…In our study, the mean duration of analgesia was more in group A (instillation group) compared to group B (infiltration group) and the difference was statistically significant between both the groups. The findings in our study correlate to the study done by Bhattarai et al, who reported the duration of postoperative analgesia more in patients who received both intraperitoneal instillation and periportal infiltration undergoing laparoscopic cholecystectomy followed by patients in instillation group and shortest duration in infiltration group patients [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the mean duration of analgesia was more in group A (instillation group) compared to group B (infiltration group) and the difference was statistically significant between both the groups. The findings in our study correlate to the study done by Bhattarai et al, who reported the duration of postoperative analgesia more in patients who received both intraperitoneal instillation and periportal infiltration undergoing laparoscopic cholecystectomy followed by patients in instillation group and shortest duration in infiltration group patients [ 14 ].…”
Section: Discussionsupporting
confidence: 91%